11-3(x-1)=6+x

Simple and best practice solution for 11-3(x-1)=6+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-3(x-1)=6+x equation:


Simplifying
11 + -3(x + -1) = 6 + x

Reorder the terms:
11 + -3(-1 + x) = 6 + x
11 + (-1 * -3 + x * -3) = 6 + x
11 + (3 + -3x) = 6 + x

Combine like terms: 11 + 3 = 14
14 + -3x = 6 + x

Solving
14 + -3x = 6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
14 + -3x + -1x = 6 + x + -1x

Combine like terms: -3x + -1x = -4x
14 + -4x = 6 + x + -1x

Combine like terms: x + -1x = 0
14 + -4x = 6 + 0
14 + -4x = 6

Add '-14' to each side of the equation.
14 + -14 + -4x = 6 + -14

Combine like terms: 14 + -14 = 0
0 + -4x = 6 + -14
-4x = 6 + -14

Combine like terms: 6 + -14 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2

See similar equations:

| 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 | | 35x^4-2x^2-1=0 |

Equations solver categories